Trajectories and predictors of financial toxicity in breast cancer patients: A multicenter longitudinal study in China - Yi Kuang; Jiajia Qiu; Ye Liu; Sijin Guo; Ting Chen; Lichen Tang; Winnie K.W. So; Weijie Xing (Breast)
Background: Patients with breast cancer experience varying levels of financial toxicity (FT), but the factors contributing to sustained financial toxicity remain poorly understood. Methods: This longitudinal study was conducted from November 2022 to March 2024 in China. Participants were recruited from four Tertiary Level A hospitals using convenient sampling. FT was assessed using the Comprehensive Score for Financial Toxicity (COST) at baseline (T1), 3 months (T2), 6 months (T3), and 12 months (T4) post-surgery. Growth Mixture Modeling was used to identify the different trajectories of the FT. Multivariable logistic regression were employed to explore the predictive factors with different trajectory categories. Results: Among 378 participants (all women; median [SD] age, 48.9 [9.97] years), the COST score was lowest at T2. Three distinct FT trajectories were identified: 91 patients (24 %) in the ''Severe FT with Gradual Relief'' group (trajectory 1), 190 patients (50 %) in the ''Persistently Low-Level FT'' group (trajectory 2), and 97 patients (26 %) in the ''Moderate FT with Gradual Worsening'' group (trajectory 3). Using trajectory 2 as the reference, predictors for trajectory 1 included symptom burden, location, cancer stage, cost-related health literacy, resilience, and difficulty affording basic expenses. For trajectory 3, predictors included monthly household income, symptom burden, location, and cancer stage. Conclusions: The FT experienced by breast cancer patients changes over time and follows distinct dynamic trajectories, influenced by multiple factors. In future clinical practice, early identification and intervention for high-risk FT groups should be prioritized.